2019
DOI: 10.1097/ta.0000000000002101
|View full text |Cite
|
Sign up to set email alerts
|

Massive transfusion protocols in nontrauma patients: A systematic review and meta-analysis

Abstract: Background Massive bleeding is a major cause of death both in trauma and non-trauma patients. In trauma patients, the implementation of massive transfusion protocols (MTP) led to improved outcomes. However, the majority of patients with massive bleeding are non-trauma patients. Objectives To assess if the implementation MTP in non-trauma patients with massive bleeding leads to improved survival. Data sources National Library of Medicine's Medline database (PubMed). Study eligibility criteria Original research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…Massive bleeding, independent of its etiology (trauma, obstetrical or surgical), usually includes high ratio FFP transfusion guided by institutional massive transfusion protocols, based on a large body of evidence favoring plasma against coagulation factor-free resuscitation uids 11,18 . This hemostatic resuscitation concept, however, is insu cient to avoid massive transfusion-associated multifactor coagulopathies 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Massive bleeding, independent of its etiology (trauma, obstetrical or surgical), usually includes high ratio FFP transfusion guided by institutional massive transfusion protocols, based on a large body of evidence favoring plasma against coagulation factor-free resuscitation uids 11,18 . This hemostatic resuscitation concept, however, is insu cient to avoid massive transfusion-associated multifactor coagulopathies 19 .…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that one should not assume that the transfusion of a high plasma to pRBC ratio will always benefit all patient groups. Recent meta-analysis [16] reported that the non-significant effect of MTP on death rate and delayed MTP activation in nontrauma patients may have affected the result. This delay might result from the unclear actual onset of bleeding in patients with non-traumatic massive hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Massive bleeding, independent of its etiology (trauma, obstetrical or surgical), usually includes high ratio FFP transfusion guided by institutional MTPs, based on a large body of evidence favoring plasma against coagulation factor-free resuscitation uids 11,18 . This hemostatic resuscitation concept however is insu cient to avoid MT associated multifactor coagulopathies 19 .…”
Section: Discussionmentioning
confidence: 99%